Consumer perceptions of stingrays in coastal areas of Indonesia - DATI NAWASTUTI; DWIDJONO HADI DARWANTO; JANGKUNG HANDOYO MULYO; SUADI SUADI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Nawastuti D, Darwanto DH, Mulyo JH, Suadi. 2023. Consumer perceptions of stingrays in coastal areas of Indonesia. Biodiversitas 24: 6844-6851. Stingray populations harvested for food may pose risks to food security and conservation goals. The purpose of this research is (i) to determine the type of fish product based on how consumers obtain the product, (ii) to determine the gender of consumers based on the type of product, and (iii) ii) to determine the type of fish product for consumption purposes. Primary data were collected from Google Forms and followed by interviews with selected households. The number of respondents was 125 people from Java Island, Timor Island, Sumba Island, Adonara Island, Lembata Island, Bangka Belitung Island and Flores Island. The information obtained was investigated using Chi-square analysis to understand consumer preferences for fish consumption using an adaptation of SPSS 25 programming. The results of the research show that there are two relationships, namely (i) the type of fish product has a significant relation to fishing, the way consumers fish, the fishery products they buy and (ii) consumer gender has a significant relationship with product type because male consumers find it easier to get stingrays by fishing so they are easier to consume individually, in groups, or to sell. A proper understanding of gender differences in stingray consumption can help determine the sustainability of stingray fisheries in a region because it can be known exactly who can access sustainable food. Although there are several types of stingrays that are protected, other types of stingrays should not be consumed. The results we obtained can be useful for increasing public awareness regarding the use of fish catching and its impact on the carrying capacity of fisheries in Indonesia.